1H-n.m.r. evaluation of the ferricytochrome c-cardiolipin interaction. Effect of superoxide radicals. - Soussi, B (1990)
The interaction between ferricytochrome c and cardiolipin was investigated by 1H n.m.r. at 270 MHz. From the phospholipid-induced changes of the protein spectral features it is concluded that the first 2 equivalents of cardiolipin cause a conformational change at the lower part of the solvent-exposed haem edge, involving a rearrangement of the hydrogen-bond interactions of propionate 6, thus partly accounting for the lowered redox potential of cytochrome c in the presence of cardiolipin. The increased value for the pK of the alkaline isomerization of ferricytochrome c shows that cardiolipin stabilizes the native structure of the protein, indicating that the oxidized form assumes ferrocytochrome c-like properties. Peroxidation of cardiolipin by superoxide radical ions drastically decreases the protein binding to this phospholipid. The implications of this finding, and the likelihood of the ternary cytochrome c-cardiolipin-cytochrome c oxidase complex, for the binding of cytochrome c to cytochrome c oxidase in vivo, are discussed in relation to peroxidative damage following ischaemia and reperfusion.